Dampak Pembiayaan Murabahah, Mudharabah, dan Musyarakah pada Profitabilitas Bank Umum Syariah - Anggita Dyah Primasari; Zaky Machmuddah; Dwiarso Utomo (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2024)
The purpose of this study is to examine the effect of financing for Islamic Commercial Banks (BUS) on profitability. The financing includes murabahah, mudharabah, and musyarakah financing. BUS is used as the research population, for the sample is selected according to the established criteria. SPSS version 20 is used as a data processing tool. The findings of the study indicate that only mudharabah financing affects profitability. While murabahah financing and musyarakah financing do not affect profitability. The implication of this study is the importance of BUS to pay attention to the type of financing carried out because it will affect profitability, considering that the Islamic banking business in Indonesia has grown quite rapidly and is competitive.